Paralleling technique for frenectomy and oral hygiene evaluation after frenectomy - Shahabe Saquib Abullais; Nitin Dani; Priyanka Ningappa; Kapil Golvankar; Amit Chavan; Nikhil Malgaonkar; Anup Gore (Wolters Kluwer Medknow Publications, 2016)
Background: High frenum attachment is a very common problem in the population. Various conventional techniques are available which has certain disadvantages; in addition to that high frenum also hinders oral hygiene maintenance. This study aims to evaluate patient's response to two different frenectomy technique, and oral hygiene maintenance before and after frenectomy. Materials and Methods: Twenty patients with high labial frenum were randomly selected from the outpatient department. Patients were divided into two groups according to the technique used. Each group contained ten patients. One group was treated by "conventional scalpel technique" and other group by "new paralleling technique". To evaluate patients response, visual analogue scale for pain and speech were taken at first postoperative day, 1-week and 1-month. In other part of the study the oral hygiene maintenance was evaluated by using plaque and gingival bleeding index at baseline before frenectomy, 1-week and 1-month after frenectomy. Results: Results showed that new paralleling technique for frenectomy causes less postoperative discomfort and also there was significant improvement in the oral hygiene maintenance by the patient after frenectomy. Conclusion: High maxillary frenum causes hindrance in oral hygiene maintenance. Paralleling technique for frenectomy causes less discomfort to the patient during healing phase when compared with the conventional technique.